FWD: Customer-centric marketing in online insurance - LUI, Patricia (Institutional Knowledge at Singapore Management University, 2020)
In November 2019, David Broom, Chief Marketing Officer of FWD Singapore, replayed a commercial ad clip of his company, as he ruefully considered the competitiveness of the insurance market in Southeast Asia. Building competitive resilience in a cutthroat market dominated by large traditional insurance players was a constant challenge for FWD. Although his company had launched innovative products in the market with improved claims processes, competitors had quickly replicated the product features and launched similar products. FWD had launched its direct-to-consumer business in September 2016 with the aim of changing the way people felt about insurance by leveraging technology to deliver products that were relevant, easy to understand, and well-priced. The direct-to-consumer business focused on life and general insurance products like direct-term life, car, travel, personal accident, and maid insurance. All FWD products were sold online, making it one of the first completely online insurance companies in the region. The company had implemented an online underwriting system, and mobile technology solutions for claims processing. FWD was also the first corporate health insurer in Southeast Asia to adopt two AI solutions – one to read documents and another to assess corporate claims (detecting fraud waste and possible abuse). And yet, despite its best efforts to leverage technology, FWD found that technology alone yielded a very slippery slope as a competitive advantage. Broom brainstormed with his colleagues for hooks that would provide FWD with that practically difficult “oomph factor” known as sustainable competitive advantage. What could be their competitive strategy? This case can be used to cover concepts related to Services Marketing in a highly competitive market with evolving technologies and customer needs. Central to the case are the dilemmas of a start-up firm in an oligopoly where product differentiation is difficult to maintain. Students will learn about the strategies used in positioning services, designing service processes and crafting the service environment. Issues related to delivering services through electronic channels are also discussed.